Linguo-stylistic peculiarities of repetitions in English aviation radiotelephony discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The role and linguo-stylistic peculiarities of repetitions in English aviation radiotelephony discourse are determined in the article. Particular attention is focused on lexical, syntactic, lexical-syntactic and phrase repetitions, and the phenomenon of syntactic parallelism as means of simplifying the understanding between pilots and air traffic controllers.
Keywords: Aviation English discourse; radiotelephony; linguo-stylistic peculiarities; professional communication